2018
DOI: 10.1038/s41394-018-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of Friedreich’s Ataxia: a report of two cases

Abstract: Although there is no cure that can alter the natural course of the disease physiotherapy, management of spasticity and neuropathic pain, symptomatic treatment of heart failure and diabetes and nursing care can grant the patients quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Both were wheelchair-bound requiring assistance with ADLs. The authors found that the management of spasticity, neuropathic pain, and the symptomatic treatment of heart failure and diabetes with the help of nursing care improved the quality of life of these patients [12]. This emphasizes the importance of support systems and coordinated care for patients with FRDA [6,12].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both were wheelchair-bound requiring assistance with ADLs. The authors found that the management of spasticity, neuropathic pain, and the symptomatic treatment of heart failure and diabetes with the help of nursing care improved the quality of life of these patients [12]. This emphasizes the importance of support systems and coordinated care for patients with FRDA [6,12].…”
Section: Discussionmentioning
confidence: 98%
“…Diabetes is independently associated with worse functional status among patients with FRDA [12]. Given this, many patients have a reduced ability to perform activities of daily living (ADLs) and adhere to medication without assistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation